KEDUDUKAN KURATOR KOPERASI SIMPAN PINJAM INTIDANA YANG BATAL DIPAILITKAN (PUTUSAN MAHKAMAH AGUNG NOMOR 43 PK/PDT.SUS- PAILIT/2022): Position of the Intidana Savings and Loans Cooperative which was canceled and bankrupted (Supreme Court decision Number 43 PK/Pdt.Sus-Pailit/2022) - Yurico Berthan Sagawa; Heru Pringgodani Sanusi (AMICUS CURIAE, 2025)
This study discusses the importance of clarity regarding the legal standing and fee determination of bankruptcy receivers (curators) in the event of a bankruptcy status revocation, as seen in the Supreme Court Decision No. 43 PK/Pdt.Sus-Bankruptcy/2022. In bankruptcy proceedings, the curator is responsible for managing and settling the debtor’s assets. The issue identified in this research is the curator’s legal position toward KSP Intidana after its bankruptcy was annulled, and whether the curator’s fee complies with the applicable regulations. This study uses a qualitative method with a descriptive analytical approach. Legally, the curator loses the formal standing to continue asset settlement following the revocation of the bankruptcy status, yet remains obligated to prepare an accountability report and return the managed assets to the debtor. Based on the research findings and conclusion, it can be concluded that the curator’s actions during the bankruptcy period remain valid as long as they are based on a prevailing court decision. Nevertheless, there is a need to evaluate the fee determination to align with the principles of justice and proportional burden-sharing among the involved parties.